Analisis Pengaruh Experiental Marketing terhadap Loyalitas Pelanggan Melalui Brand Image dan Customer Satisfaction (Studi pada Pelanggan 9 Typical Cafe Semarang) - Wasistho, Andhika Satya; Rahardjo, Susilo Toto (Diponegoro Journal of Management, 2023)
BSTRACT The coffee shop industry that provides food and beverages in the city of Semarang is increasingly in demand. The development of the times and the increasing needs of the community in the city of Semarang, has an impact on the coffee shop business sector where business actors compete to create a more modern and more comfortable place design without removing the cafe concept such as a place to relax and enjoy coffee. It is important for coffee shop business owners, especially 9Typical, to be able to maintain customer loyalty by providing experiential marketing, brand image, and superior customer satisfaction to survive in the midst of business competition. This study uses regular consumers of 9Typical Cafe Semarang, then sampling is done using purposive sampling and has several criteria. The sample in this study amounted to 150 respondents aged more than 17 years and had visited and purchased at 9Typical at least 2 (two) times in the last 3 (three) months. The data collected was analyzed using the Structural Equation Model (SEM) method and processed with AMOS software. The results of this study indicate that experiental marketing has a significant positive effect on brand image, experiental marketing has a significant positive effect on customer satisfaction, experiental marketing has a significant positive effect on customer loyalty, brand image has a significant positive effect on customer loyalty, and customer satisfaction has a significant positive effect on customer loyalty